PENGEMBANGAN BAHAN AJAR PENDIDIKAN MATEMATIKA 1 UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN MAHASISWA PGSD UNIVERSITAS KUNINGAN - Aan Nurhasanah (EduHumaniora: Jurnal Pendidikan Dasar, 2017)
Abstract:. This research and development aims to produce teaching materials for improving the quality of learning of Elementary Teacher Education students of University of Kuningan especially on Mathematics Education I course. This research using Dick and Carey Research & Development model. The research stages are (a) the stages of analysis performed on the curriculum, the needs of the students and the lecturers' needs. (B) the product development stage is a lecture module, which is analyzed by expert team. (C) the pilot stage, this stage is done if the expert team has finished validating the teaching materials to be used in the lecture process. The results showed that the teaching materials developed can improve the quality of learning with the average achievement of pre-test of 65.76 while the mean post-test value of 78.20. Then the results of the observer assessment showed that 78% of students follow the course activities well.